Controllable multicompartment morphologies from cooperative self-assembly of copolymer–copolymer blends. Issue 35 (2nd August 2017) - Wang, Zhikun; Sun, Shuangqing; Li, Chunling; Hu, Songqing; Faller, Roland
Abstract : Multicompartment nanostructures, such as microcapsules with clearly separated shell and core, are not easily accessible by conventional block copolymer self-assembly. Abstract : Multicompartment nanostructures, such as microcapsules with clearly separated shell and core, are not easily accessible by conventional block copolymer self-assembly. We assess a versatile computational strategy through cooperative assembly of diblock copolymer blends to generate spherical and cylindrical compartmentalized micelles with intricate structures and morphologies. The co-assembly strategy combines the advantages of polymer blending and incompatibility-induced phase separation. Following this strategy, various nanoassemblies of pure AB, binary AB/AC and ternary AB/AC/AD systems such as compartmentalized micelles with sponge-like, Janus, capsule-like and onion-like morphologies can be obtained. The formation and structural adjustment of microcapsule micelles, in which the shell or core can be occupied by either pure or mixed diblock copolymers, were explored. The mechanism involving the separation of shell and core copolymers is attributed to the stretching force differences of copolymers which drive the arrangement of different copolymers in a pathway to minimize the total interfacial energy. Moreover, by adjusting block interactions, an efficient approach is exhibited for regulating the shell or core composition and morphology in microcapsule micelles, such as the transition from the "pure shell/mixed core" morphology to the "mixed shell/pure core" morphology in the AB/AC/AD micelle. This mesoscale simulation study identifies the key factors governing co-assembly of diblock copolymer blends and provides bottom-up insights towards the design and optimization of new multicompartment micelles.